Environmental Conservation Based on Community Empowerment: Case Study in Toba Caldera UNESCO Global Geopark (Jurnal Bina Praja, 2022)
Toba Caldera UNESCO Global Geopark (TCUGG) has not only geological phenomena of international geological significance value but also has outstanding universal value by the United Nations Educational, Scientific and Cultural Organization (UNESCO). The establishment of TCUGG as a national priority and the Lake Toba Authority Agency is a serious commitment from the government to develop this region. Although it is now a super-priority tourism destination, over the last six decades, the water level of Lake Toba has decreased significantly by 2.4 cm per year from 1957 to 2016. The environmental quality index shows a decline from year to year, and environmental conditions of Lake Toba are already very severe due to various factors. The government and local communities are still running independently for the conservation agenda. This empirical research uses a mixed method of sequential explanation. The main objective of the research is to analyze the determinants of local people's choices to participate in conservation activities in TCUGG. From the research results, the significant factors that determine the local communities' participation in conservation activities are water availability, incentives, suitability of seeds, trust level for the initiator, and the success rate of previous conservation. Society does not need promises or rhetoric, especially for those who have participated before and experienced low success rates. Application of reward and punishment as an incentive for the community to participate in conservation activities and to further encourage their motivation. The main key is to serve the needs of the community in conservation practices.